Sosialisasi Literasi Digital Sebagai Upaya Pencegahan Penyalahgunaan Obat Bebas pada Remaja - HOS, Jamaluddin; Mahmudah, Rifa’atul; Sida, Nurramadhani A; Shalihah, Rifa’atus (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The misuse of over-the-counter (OTC) medicines among adolescents is increasing, driven by high exposure to social media and low digital literacy. Teenagers often consume health information without verification, including content promoting inappropriate medication use. This community engagement activity aimed to enhance students’ understanding of the risks associated with OTC medicine misuse and to strengthen their digital health literacy. The program was conducted at SMAN 4 Kendari with 50 participants using interactive lectures, group discussions, educational social-media videos, and the distribution of leaflets and educational souvenirs. The results showed high student enthusiasm, reflected in numerous questions and active responses during discussions. Verbal evaluation indicated improved understanding of the dangers of OTC misuse and the ability to identify non-credible health content. Overall, the activity effectively improved adolescents’ medicine literacy and digital literacy, supporting efforts to prevent OTC medicine misuse in the school environment.